Description of a new species of Meganola Dyar, 1898 (Lepidoptera, Nolidae, Nolinae), with new records of Meganola in China - Zhang, Bei-Bei; Hu, Yan-Qing (Zootaxa, 2022)
The genus Meganola Dyar, 1898 was described from North America with type species, Meganola conspicua Dyar, 1898 by monotype. Poole (1898) assigned to it all taxa of Roeselia Hübner (which is currently a synonym of Nola Leach), except those of Sarbena Walker and Proneca Swinhoe. Meganola is widely distributed in the Old and New Worlds (Hacker et al., 2012; László et al., 2015).